Inappropriate antimicrobial use in Turkish pediatric hospitals: A multicenter point prevalence survey - Ceyhan, M.; Yildirim, I.; Ecevit, C.; Aydogan, A.; Ornek, A.; Salman, N.; Coskun, Y. (Elsevier Sci Ltd, 2010)
Objectives: Although well-defined principles of rational antimicrobial use are available, inappropriate prescribing patterns are reported worldwide. Accurate information on the usage of antimicrobials, including factors associated with and influencing their use, is valuable for improving the quality of prescription practices. Methods: In this cross-sectional point prevalence survey, data on patients hospitalized in 12 different children's hospitals were collected on a single day. Appropriateness of prescription was compared between the types of antimicrobials prescribed, indications, wards, and presence of/consultation with an infectious disease physician (IDP). Results: A total 711 of 1302 (54.6%) patients evaluated were receiving one or more antimicrobial drugs. The antimicrobial prescription rate was highest in pediatric intensive care (75.7%) and lowest in the surgery wards (37.0%). Of the 711 patients receiving antimicrobials, 332 patients (46.7%) were found to be receiving at least one inappropriately prescribed drug. Inappropriate use was most frequent in surgery wards (80.2%), while it was less common in oncology wards (31.8%; p < 0.001). Respiratory tract infection was the most common indication for antimicrobial use (29.4%). Inappropriate use was more common in deep-seated infections (54.7%) and respiratory infections (56.5%). Fluoroquinolones were used inappropriately more than any other drugs (81.8%, p = 0.021). Consultation with an IDP appears to increase appropriate antimicrobial use (p = 0.008). Conclusions: Inappropriate antimicrobial use remains a common problem in Turkish pediatric hospitals. Consultation with an IDP and prescribing antimicrobial drugs according to microbiological test results could decrease the inappropriate use of antimicrobials. (C) 2009 International Society for Infectious Diseases. Published by Elsevier Ltd. All rights reserved.
Keywords: Inappropriate antimicrobial usage; Point prevalence; Pediatric hospitals